Estimation of the present mammal fauna situation in the Moc Chau district, Son La province - Viet, Tran Hong; Hai, Tran Hong; Nha, Pham Van (Academia Journal of Biology, 2014)
The article presents the estimation of the present mammal fauna situation in the Mocchau district, Sonla province, which includes 81 species and subspecies belonging to 56 genera, 24 families and 8 orders of mammals in Vietnam now. On those basics, we appreciate the actuality and suggest some methods to protection. The abundance of this mammal population are shown in 5 levels as follows. In the numerous level, there are 10 species which make up 12.35% of the mammal species number in the district: in the medium level, there are 16 species (19.75%); in the little level, there are 37 species (45.68%); in the rare level, there are 15 species (18.52%) and in the extinct level, there are 6 species (7.41%). There are 29 precious and rare mammal species and subspecies which make up 37.66% of the mammal species number in the district; among them, there are 93.1% species which have the abundance under the medium level. In general, the Mocchau mammal fauna is not rich, with 67.9% species which have the number under the medium level and 7.41% species which are extincted. So, it needs to protect this fauna timely and effectively.